Applied biopolymer technology and bioplastics : sustainable development by green engineering materials - Rawat, Neha Kanwar; Volova, Tatiana G.; Haghi, A. K. (Palm Bay, FL, USA ; Burlington, ON, Canada : Apple Academic Press ; Boca Raton, FL, USA ; Abingdon, Oxon, UK : CRC Press, 2021)
"With growing concern for the environment and the rising price of crude oil, there is increasing demand for non-petroleum-based polymers from renewable resources. Recognizing emerging developments in biopolymer systems research, this book brings together a number of key biopolymer and bioplastic topics in one place. The book highlights the importance and impact of eco-friendly green biopolymers and bioplastics, both environmentally and economically. It provides important insight into the diversity of polymers obtained directly from, or derived from, renewable resources. This volume, Applied Biopolymer Technology and Bioplastics: Sustainable Development by Green Engineering Materials, will be valuable for a broad audience of engineers and scientists, especially those designing with biopolymers and biodegradable plastics, or evaluating the options for switching from traditional plastics to biopolymers. The content of this book will prove useful for students, researchers, and professionals working in the field of green technology."--
Processing Relation to Rheological Behavior of Some Systems Containing Green Polymers / Andreea Irina Barzic -- Properties of the Magnetic Polymer Nanocomposites in Magnetic Fields / Jimsher Aneli and Grigor Mamniashvili -- Microbial Fuel Cell: A Green Microbial Approach for Production of Bioelectricity Using a Conducting Polymer / Swapnali A. Patil, Akshada A. Bakliwal, and Swati G. Talele -- Sustainability of the Tire Industry: Through a Material Approach / Sanjit Das, Hirak Satpathi, S. Roopa, and Saikat Das Gupta -- Silk: An Explorable Biopolymer in the Biomedical Arena / Athira John, Ananthu Prasad, and Neha Kanwar Rawat -- Influence of Nanotechnology on Prevention of Biofouling in Aquaculture Cage Nets: Green Conducting Polymers and Their Significance in Case Studies / P. Muhamed Ashraf -- Biodegradable PHAs: Promising "Green" Bioplastics and Possible Ways to Increase Their Availability / Tatiana Gr. Volova, Evgeniy G. Kiselev, Aleksey V. Demidenko, Svetlana V. Prudnikova, Ekaterina I. Shishatskaya, and Sabu Thomas -- Membrane Technology for Green Engineering / Supriya Dhume and Yogesh Chendake -- Green Hydrogen Energy: Storage in Carbon Nanomaterials and Polymers / Brahmananda Chakraborty and Gopal Sanyal -- Self-Assemblies of Macromolecular Systems Containing Green Polymers / Andreea Irina Barzic, Raluca Marinica Albu, and Cristian Logigan.
OCLC-licensed vendor bibliographic record.
Keywords: Biopolymers; Biodegradable plastics; Green technology; Sustainable engineering; TECHNOLOGY / Textiles & Polymers; TECHNOLOGY / Material Science